2019
DOI: 10.1108/ijced-03-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

School feeding as a social protection programme or a political largesse: a review

Abstract: Purpose In an attempt to tackle the incidence of poverty and social exclusion in the Ghanaian society, a number of social protection programmes including the school feeding programme is introduced. The programme is designed to cater for the extreme poor and as well encourage enrolment and attendance in the country. The purpose of this paper is to assess the intention or objective for which the programme is initiated and the realities on the ground. It looks at whether the current beneficiaries are the extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
3
0
4
Order By: Relevance
“…Crianças famintas têm menor energia e habilidades de pensamento são afetadas, gerando deficit de concentração. A fome impede que crianças pobres ou famintas tenham direito à educação e é um dos principais alvos de programa de alimentação escolar (IDDRISU et al, 2019).…”
Section: Programas De Alimentação Escolar No Mundounclassified
See 2 more Smart Citations
“…Crianças famintas têm menor energia e habilidades de pensamento são afetadas, gerando deficit de concentração. A fome impede que crianças pobres ou famintas tenham direito à educação e é um dos principais alvos de programa de alimentação escolar (IDDRISU et al, 2019).…”
Section: Programas De Alimentação Escolar No Mundounclassified
“…Países africanos têm procurado ampliar programas de alimentação escolar baseados na experiência do Brasil, que reduziu os impactos da pobreza por meio da alimentação escolar. O Brasil é considerado modelo em todo o mundo na implementação do programa de alimentação escolar sem interferência política (IDDRISU et al, 2019;SONNINO;LOZANO TORRES;SCHNEIDER, 2014).…”
Section: Programas De Alimentação Escolar No Mundounclassified
See 1 more Smart Citation
“…Given the educational gap between the southern sector and the northern sector of the country in Ghana, it drives public action against illiteracy and inequality in access to basic education [11]. The move to eliminate illiteracy in the Ghanaian society is the objective of successive governments.…”
Section: Ghana Education Service Involvementmentioning
confidence: 99%
“…Salifu, Boateng and Kunduzore (2018) have also discussed the contribution of Ghana's feeding programme towards the achievement of free compulsory basic education in Ghana, and found that it has had a positive influence on school enrolment and retention; however, it is silent on what pertains in non-participating schools in the same community or towns. Iddrisu et al (2019) have also questioned the link between the selection of participating schools and the objective of the programme to reduce poverty, and have pointed to problems associated with selection of schools.…”
Section: Alimentação Escolar Do Ganamentioning
confidence: 99%